Association between parental practices in child feeding, use of electronic devices and food selectivity in childhood - Giovanna Peres Loureiro; Cátia Regina Ficagna; Paula Ruffoni Moreira; Leandro Meirelles Nunes; Juliana Rombaldi Bernardi (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze the relationship between parental practices, screen time, and food selectivity in children at 12 months of age. Methods: a cross-sectional study nested within a randomized clinical trial. In addition to sociodemographic information and the child’s nutritional status, variables selected included the degree of food selectivity, parental practices (parent-centered practices/high control, parent-centered practices/contingency management, child-centered practices), obtained through validated questionnaires: The Child Eating Behavior Questionnaire and the Parental Feeding Style Questionnaire, as well as the use of electronics by children during meals. Crude and adjusted linear regression analysis were performed to assess the association between parental practices and food selectivity. Results: the use of parent-centered/contingency management practices were higher among female infants (p=0.034) and children classified as eutrophic (p=0.021). Parent-centered/high control practices and child-centered practices were positively associated with food selectivity (p=0.037 and p=0.048, respectively). Conclusions: the evidence that parental feeding practices are associated with a child’s food selectivity highlights the importance of initiatives aimed at providing appropriate guidance to parents during this stage of life.